GENEALOGI KUASA DAN PENGETAHUAN: DEKONSTRUKSI PERAN MADRASAH SEBAGAI INSTRUMEN HEGEMONI IDEOLOGI NEGARA PADA MASA DINASTI ABBASIYAH - Eko Ngabdul Shodikin; Sa’adi; Rahmat Hariyadi (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
The struggle between educational institutions and political power structures is a historical phenomenon that demands a critical reading of the power-knowledge relationship within the classical Islamic civilizational tradition. This research aims to deconstruct the role of the madrasah as an instrument of state ideological hegemony during the Abbasid Dynasty. Utilizing a qualitative-historical design with a Foucauldian genealogical approach, this study uncovers how the madrasah was operated as a discursive apparatus to produce a "regime of truth". Data were sourced from a corpus of primary texts, including classical Arabic manuscripts, waqfiyah documents, and prosopographical analysis of scholarly biographies. The research findings indicate that: (1) the institutionalization of the madrasah, particularly the Nizamiyah network, functioned as a technology of power to consolidate Sunni orthodoxy and eliminate alternative narratives; (2) the system of waqf patronage and the bureaucratization of the ijazah created a structural dependence of the ulema on the state, thereby limiting intellectual autonomy ; and (3) there were dynamics of resistance from alternative institutions, such as Sufi ribats, which offered spiritual autonomy outside of state hegemonic control. This research concludes that the madrasah was not merely a neutral institution for knowledge transmission, but rather a technology of governmentality that regulated religious subjects to align with the state’s political agenda. The implications of this study offer a critical framework for the analysis of the politics of knowledge within contemporary Islamic educational institutions. ABSTRAK Pergumulan antara institusi pendidikan dan struktur kekuasaan politik merupakan fenomena historis yang menuntut pembacaan kritis terhadap relasi kuasa-pengetahuan dalam tradisi peradaban Islam klasik. Penelitian ini bertujuan untuk mendekonstruksi peran madrasah sebagai instrumen hegemoni ideologi negara pada masa Dinasti Abbasiyah. Dengan menggunakan desain kualitatif-historis dan pendekatan genealogi Foucauldian, studi ini membongkar bagaimana madrasah dioperasikan sebagai aparatus diskursif untuk memproduksi "rezim kebenaran". Data bersumber dari korpus teks primer seperti manuskrip Arab klasik, dokumen waqfiyah, serta analisis prosopografis terhadap biografi ulama. Temuan penelitian menunjukkan bahwa: (1) institusionalisasi madrasah, khususnya jaringan Nizamiyah, berfungsi sebagai teknologi kekuasaan untuk mengonsolidasi ortodoksi Sunni dan mengeliminasi narasi alternatif; (2) sistem patronase wakaf dan birokratisasi ijazah menciptakan ketergantungan struktural ulama terhadap negara yang membatasi otonomi intelektual; dan (3) terdapat dinamika resistensi dari institusi alternatif seperti ribat sufi yang menawarkan otonomi spiritual di luar kontrol hegemonik negara. Penelitian ini menyimpulkan bahwa madrasah bukan sekadar lembaga transmisi pengetahuan netral, melainkan teknologi governmentality yang mengatur subjek religius agar selaras dengan agenda politik negara. Implikasi studi ini menawarkan kerangka kritis bagi analisis politik pengetahuan dalam institusi pendidikan Islam kontemporer.